Development and validation of sensitive real-time RT-PCR assay for broad detection of rabies virus - (:unkn) unknown (My University, 2017)
Rabies virus (RABV) remains one of the most important global zoonotic pathogens. RABV causes rabies, an acute encephalomyelitis associated with a high rate of mortality in humans and animals and affecting different parts of the world, particularly in Asia and Africa. Confirmation of rabies diagnosis relies on laboratory diagnosis, in which molecular techniques such as detection of viral RNA by reverse transcription polymerase chain reaction (RT-PCR) are increasingly being used. In this study, two real-time quantitative RT-PCR assays were developed for large-spectrum detection of RABV, with a focus on African isolates. The primer and probe sets were targeted highly conserved regions of the nucleoprotein (N) and polymerase (L) genes. The results indicated the absence of non-specific amplification and cross-reaction with a range of other viruses belonging to the same taxonomic family, i.e. Rhabdoviridae, as well as negative brain tissues from various host species. Analytical sensitivity ranged between 100 to 10 standard RNA copies detected per reaction for N-gene and L-gene assays, respectively. Effective detection and high sensitivity of these assays on African isolates showed that they can be successfully applied in general research and used in diagnostic process and epizootic surveillance in Africa using a double-check strategy.
Keywords: African Research